Combustion engineering issues for solid fuel systems - Miller, Bruce G.; Tillman, David A. (Academic Press/Elsevier, 2008)
"Design, construct and utilize fuel systems using this comprehensive reference work. Combustion Engineering Issues for Solid Fuel Systems combines modeling, policy/regulation and fuel properties with breakthroughs in solid fuel combustion for electricity generation and industrial applications. Combustion Engineering Issues for Solid Fuel Systems will be of use to practicing engineers as well as managers and policy makers."--Jacket